EFFECTIVENESS OF PUNJAB EDUCATION AND ENGLISH LANGUAGE INITIATIVE (PEELI) IN ENHANCING ENGLISH LANGUAGE SKILLS OF PUBLIC-SCHOOL TEACHERS OF PUNJAB - Fatima Zafar Baig, Muhammad Javed Aslam, Muhammad Hannan Naseer, Zafar Iqbal (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The study aims to evaluate the effectiveness of the Punjab Education and English Language Initiative (PEELI) project in enhancing the English language skills of teachers who are teaching their subjects in the school education department, Punjab. From primary to elementary level in Punjab, the public-school teachers face an inability to grasp English language skills to a sufficient degree and, therefore, could not impart these skills in turn to the respective students. The government of Punjab, with the collaboration of The British Council, initiated a "Punjab Education and English language Initiative" (PEELI) to enhance the language skills of teachers (number 300,000) for better student learning outcomes. The present study examines one of the six components of PEELI, i.e., the Training Component. The project is initiated with the School Education Department (SED) Punjab, one of the world's largest educational systems. The study is mainly based on Kachru's (1985) theory that defines English language development through age. PEELI Training is conducted by the British Council, which belongs to the United Kingdom and is run by native English speakers. The UK, according to Kachru, is a state that is "a norm providing state" for English, while Pakistan being an erstwhile colonial state of the UK, is a norm developing country. The joint venture of GOP and BC is a combination of norm-providing and norm-developing countries to enhance the English language skills of the school education department's in-service teachers. For this purpose, the study adopts a quantitative approach combined with a survey to collect data. A descriptive analysis of the acquired data from the survey is done by employing SPSS to reach out to the findings. The findings indicate that the project is highly effective in enhancing the ability of ESL teachers though still facing several challenges.